DECISION SUPPORT SYSTEM FOR DETERMINING THE TYPES OF PLANTS IN AGRICULTURAL LAND BY USING SIMPLE ADDITIVE WEIGHTING (SAW) - Wilda Rina Hasibuan (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2016)
The problem faced by every farmer in general, ie lack of knowledge to determine the exact species of plants and suitable for planting on a farm. Determination of the proper plant species in an area greatly affected agricultural production resulting from the land. Assessment of a farm seen from kessuaian land cover classes and characteristics of agricultural land suitability. On agricultural land characteristics specified criteria to support the assessment of a region. The criteria in question is rainfall, shape Territory / slope, soil texture, soil structure, drainage class, erodibility, soil fertility. Keputuan Support System is very useful in helping decision-makers in determining the best option. This is because the system is supported by a process of ranking the alternatives that will get the best of several alternatives. This system is presented with the Simple Additive weighting method (SAW) can complete the study by finding the weights for each attribute value then the best alternative available. The results of the assessment can be used to increase agricultural output.Keywords: Decision Support System, Simple Additive weighting, Determination Type Plants